BETA‐2 score is an early predictor of graft decline and loss of insulin independence after pancreatic islet allotransplantation. Issue 3 (13th November 2019) - Bachul, Piotr J.; Gołębiewska, Justyna E.; Basto, Lindsay; Gołąb, Karolina; Anteby, Roi; Wang, Ling‐Jia; Tibudan, Martin; Thomas, Celeste; Fendler, Wojciech; Lucander, Aaron; Grybowski, Damian J.; Dębska‐Ślizień, Alicja; et al.
Abstract : This study aimed to evaluate whether the BETA‐2 score is a reliable early predictor of graft decline and loss of insulin independence after islet allotransplantation. Islet transplant procedures were stratified into 3 groups according to clinical outcome: long‐term insulin independence without islet graft decline (group 1, N = 9), initial insulin independence with subsequent islet graft decline and loss of insulin independence (group 2, N = 13), and no insulin independence (group 3, N = 13). BETA‐2 was calculated on day 75 and multiple times afterwards for up to 145 months posttransplantation. A BETA‐2 score cut‐off of 17.4 on day 75 posttransplantation was discerned between group 1 and groups 2 and 3 (area under the receiver operating characteristic 0.769, P = .005) with a sensitivity and negative predictive value of 100%. Additionally, BETA‐2 ≥ 17.4 at any timepoint during follow‐up reflected islet function required for long‐term insulin independence. While BETA‐2 did not decline below 17.4 for each of the 9 cases from group 1, the score decreased below 17.4 for all transplants from group 2 with subsequent loss of insulin independence. The reduction of BETA‐2 below 17.4 predicted 9 (1.5‐21) months in advance subsequent islet graft decline and loss of insulin independence ( P = .03). This finding has important implications for posttransplant monitoring and patient care. Abstract : BETA‐2 score was found to be a reliable, precise, and clinically convenient tool for monitoring islet graft function based on a single, fasting blood sample, serving as an excellent screening tool predicting upcoming islet decline months in advance, allowing early implementation of new diagnostic and therapeutic tools to prevent islet graft loss.